The Optimal Age of the Second-First Language Acquisition: The Relationship of Language and Physical-Motor Development - Setiawan, Budi (Lingua Cultura, 2019)
This research highlighted the language and physical-motor relationship and aimed to find the optimal age for the beginning of the second-first language (2L1) acquisition. The respondents of this research were 50 millennial generations of Chinese families whose children were 0-5 years old. Some children could communicate in Chinese and Indonesian language. Chinese-Indonesian families were chosen by considering their bilingual. This research employed qualitative data which were collected from observations and questionnaires given to parents. The collected data were analyzed by classifying the data into some specific intervals of age based on the language milestones. This research finds that the highest frequency of the beginning in the simultaneous second-first language education is at 13-15 months. This research also proves that the age between 13-15 months is an optimal age to begin educating the second language regarded as the first language for bilingual families.